Statistics for business and economics - Newbold, Paul; Carlson, William L.; Thorne, Betty (Pearson Education, 2013)
Statistics for Business and Economics enables students to conduct serious analysis of applied problems rather than running simple canned applications. The eighth edition of this book has been revised and updated to provide students with improved problem contexts for learning how statistical methods can improve their analysis and understanding of business and economics.